Lack´s transmission from a view of Lacan´s seminar book four - Fragelli, Ilana Katz Z.; Petri, Renata (Clinical Styles. The Journal on the vicissitudes of childhood, 2004)
This paper presents a view of the Lacan’s Seminar Book Four focused on the lack’s transmission as the main point of the subject constitution throughout three logical moments: privation, frustration and castration.